2021
DOI: 10.3390/antiox10121919
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation Caused by Cisplatin Ototoxicity

Abstract: Hearing loss is a significant health problem that can result from a variety of exogenous insults that generate oxidative stress and inflammation. This can produce cellular damage and impairment of hearing. Radiation damage, ageing, damage produced by cochlear implantation, acoustic trauma and ototoxic drug exposure can all generate reactive oxygen species in the inner ear with loss of sensory cells and hearing loss. Cisplatin ototoxicity is one of the major causes of hearing loss in children and adults. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 108 publications
(138 reference statements)
0
30
0
Order By: Relevance
“…Over the past decades it became clear that oxidative stress is a common denominator of many forms of acquired sensorineural hearing loss ( Henderson et al, 2006 ; Rousset et al, 2015 ; Fetoni et al, 2019 ; Ramkumar et al, 2021 ). Noise-induced oxidative damages, including hair cell membrane lipid peroxidation or DNA oxidation, appear as early as a few hours following the insult ( Maulucci et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades it became clear that oxidative stress is a common denominator of many forms of acquired sensorineural hearing loss ( Henderson et al, 2006 ; Rousset et al, 2015 ; Fetoni et al, 2019 ; Ramkumar et al, 2021 ). Noise-induced oxidative damages, including hair cell membrane lipid peroxidation or DNA oxidation, appear as early as a few hours following the insult ( Maulucci et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin-induced oxidative stress contributes to the cellular damage of the inner ear and ototoxicity [ 9 , 19 ]. In this study, we found that hypBMSC-Exo could be considered a post-exposure treatment option to diminish the production of reactive oxygen species to alleviate hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant signaling may also be involved in the protective effect of LPZ against CIO. CDDP generates oxidative stress which leads to apoptosis and necroptosis of auditory hair cells (Ramkumar et al, 2021). LPZ can exert antioxidant effects through activation of nuclear factor erythroid 2-related factor 2 (Takagi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%